Extent of Effects of Guidance Services on the Development and Performance of College Students in Tomas Claudio Colleges - Baruel, Lilian; Dematera, Louie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to determine the extent of effects of guidance services on the development and academic performance of college students in Tomas Claudio Colleges during the School Year 2024–2025. The respondents comprised 329 college students from second to fourth year, representing various programs, and were described in terms of age, sex, civil status, year level, sibling position, monthly family income, and parents’ educational attainment and occupation. Respondents were selected through Slovin’s formula using a simple random sampling technique. A researcher-made questionnaire-checklist was utilized to assess the perceived effects of guidance services on students’ development, focusing on cognitive development, career orientation, moral development, and social development. Additionally, documentary analysis was conducted using students’ average grades from the second semester of School Year 2023–2024 as an indicator of academic performance.Findings revealed that most respondents were 19–20 years old, female, single, second-year students, first-born, belonging to a family income bracket of Php 10,000–19,999, with college graduate parents of varied occupations. Students generally agreed that guidance services positively influenced their cognitive, moral, social, and career development. No significant differences were observed in students’ perceptions based on age, sex, civil status, year level, sibling position, monthly family income, father’s educational attainment, or parents’ occupation, except for a significant difference in cognitive development based on mother’s educational attainment. Academic performance was rated as Very Satisfactory (mean = 1.76), but no significant relationship was found between perceived effects of guidance services and academic performance. Challenges encountered included busy schedules, hesitancy to share personal concerns, and fear of disclosure.The study recommends enhancing guidance programs through targeted workshops on critical thinking, career exploration, values education, and social skills development, as well as adjusting student schedules to improve access to services. Further studies may explore additional variables and strategies to optimize guidance service outcomes.
Keywords: guidance services, college students, cognitive development, career orientation, moral development, social development, academic performance